Get clear, concise, and accurate answers to your questions on IDNLearn.com. Our experts are ready to provide prompt and detailed answers to any questions you may have.

4. Which one of the following is equal to the sum [tex]\sum_{k=1}^7 729\left(3^{1-k}\right)[/tex]?

A. 1088
B. 1093
C. 1079
D. 1092


Sagot :

To solve the given problem, we need to determine the sum of the series [tex]\(\sum_{k=1}^7 729\left(3^{1-k}\right)\)[/tex].

1. Understanding the Series:
The given series is:
[tex]\[ S = \sum_{k=1}^7 729 \left(3^{1-k}\right) \][/tex]
This means:
[tex]\[ S = 729 \left(3^{1-1}\right) + 729 \left(3^{1-2}\right) + 729 \left(3^{1-3}\right) + \cdots + 729 \left(3^{1-7}\right) \][/tex]

2. Simplifying the Terms:
Each term inside the series can be simplified. When [tex]\( k = 1 \)[/tex]:
[tex]\[ 729 \left(3^{1-1}\right) = 729 \left(3^0\right) = 729 \cdot 1 = 729 \][/tex]
When [tex]\( k = 2 \)[/tex]:
[tex]\[ 729 \left(3^{1-2}\right) = 729 \left(3^{-1}\right) = 729 \cdot \frac{1}{3} = 243 \][/tex]
When [tex]\( k = 3 \)[/tex]:
[tex]\[ 729 \left(3^{1-3}\right) = 729 \left(3^{-2}\right) = 729 \cdot \left(\frac{1}{3^2}\right) = 729 \cdot \frac{1}{9} = 81 \][/tex]
When [tex]\( k = 4 \)[/tex]:
[tex]\[ 729 \left(3^{1-4}\right) = 729 \left(3^{-3}\right) = 729 \cdot \left(\frac{1}{3^3}\right) = 729 \cdot \frac{1}{27} = 27 \][/tex]
When [tex]\( k = 5 \)[/tex]:
[tex]\[ 729 \left(3^{1-5}\right) = 729 \left(3^{-4}\right) = 729 \cdot \left(\frac{1}{3^4}\right) = 729 \cdot \frac{1}{81} = 9 \][/tex]
When [tex]\( k = 6 \)[/tex]:
[tex]\[ 729 \left(3^{1-6}\right) = 729 \left(3^{-5}\right) = 729 \cdot \left(\frac{1}{3^5}\right) = 729 \cdot \frac{1}{243} = 3 \][/tex]
When [tex]\( k = 7 \)[/tex]:
[tex]\[ 729 \left(3^{1-7}\right) = 729 \left(3^{-6}\right) = 729 \cdot \left(\frac{1}{3^6}\right) = 729 \cdot \frac{1}{729} = 1 \][/tex]

3. Summing the Series:
Now, we'll add up these terms:
[tex]\[ 729 + 243 + 81 + 27 + 9 + 3 + 1 \][/tex]

4. Calculating the Sum:
[tex]\[ 729 + 243 = 972 \][/tex]
[tex]\[ 972 + 81 = 1053 \][/tex]
[tex]\[ 1053 + 27 = 1080 \][/tex]
[tex]\[ 1080 + 9 = 1089 \][/tex]
[tex]\[ 1089 + 3 = 1092 \][/tex]
[tex]\[ 1092 + 1 = 1093 \][/tex]

Therefore, the sum is [tex]\(1093\)[/tex].

Answer: B. 1093